2013
DOI: 10.4067/s0718-58392013000200004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of contrasting environments on seed composition of two quinoa genotypes: nutritional and functional properties

Abstract: Quinoa (Chenopodium quinoa Willd.) in Chile represents a source of germplasm with high nutritional value. However, there is little information available related to quinoa seed quality grown under contrasting environments. In this study we evaluated the changes on seed composition of seeds of two lowland/coastal quinoa genotypes grown under arid (Vicuña) and cold-temperate (Temuco) conditions in Chile. Results showed that in the case of 'Regalona Baer' and 'Villarrica' genotypes the arid location (with irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
52
3
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 27 publications
24
52
3
7
Order By: Relevance
“…The contrasting results of Miranda et al (2012Miranda et al ( , 2013 who reported in Chile an increase of saponin content in an arid, but irrigated environment and a decrease, in rainy environment not for all the genotypes, suggest, in agreement with Zurita et al (2014), that additional studies must be conducted to elucidate how the environmental and the genotypic effects influence the seed saponin levels.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The contrasting results of Miranda et al (2012Miranda et al ( , 2013 who reported in Chile an increase of saponin content in an arid, but irrigated environment and a decrease, in rainy environment not for all the genotypes, suggest, in agreement with Zurita et al (2014), that additional studies must be conducted to elucidate how the environmental and the genotypic effects influence the seed saponin levels.…”
Section: Resultsmentioning
confidence: 81%
“…Drought reduces by 45% the accumulation of sapogenins in quinoa seeds, based on one study of severe water deficit conducted in Southern Europe (Gomez-Caravaca et al, 2012), whereas salinity has the opposite effect (Soliz-Guerrero et al, 2002;Pulvento et al, 2012). More recently, however, a significant increase of saponins and other seed components has been reported in an arid location (irrigated) as opposed to a cold temperate climate (rainfed) site (Miranda et al, 2012;Miranda et al, 2013). Thus, the above data suggest that additional studies must be conducted to elucidate how the environmental and the genotypic effects influence the seed saponin levels (Zurita et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The highest CP content in the grain recorded by 175 kg N ha -1 treatment which was 16.5% higher than that in the control treatment, but statistically similar to 150 kg N ha -1 treatment (15.8%). The higher protein content at higher nitrogen levels was mainly due to the structural role of nitrogen in building up amino acids (Finck, 1982;Bhargava et al, 2006;Miranda et al, 2013). The progressive increase in protein contents of quinoa seed with the increasing nitrogen rates were also reported by many research workers (Jacobsen et al, 1994;Erley et al, 2005;Shams, 2012).…”
Section: Crude Protein Content Of Seedmentioning
confidence: 77%
“…The progressive increase in protein contents of quinoa seed with the increasing nitrogen rates were also reported by many research workers (Jacobsen et al, 1994;Erley et al, 2005;Shams, 2012). Erley et al (2005) informed that average CP content of quinoa cultivars (Faro and Cochabamba) increased gradually (12.3% to 14.6%, respectively) with the increasing nitrogen levels from 0 kg N to 120 kg N ha -1 and, Miranda et al (2013) reported an average CP content of 18.8% using cold resistance quinoa cultivars (Regalona Baer and Villarrica). Kakabouki et al (2014) also stated that increasing nitrogen level increased CP content of quinoa from 7% to 27% under different tillage system.…”
Section: Crude Protein Content Of Seedmentioning
confidence: 99%
“…Otros carbohidratos presentes en menores proporciones en los granos de quinoa y soja son la glucosa, fructosa, arabinosa, galactosa, sacarosa, maltosa y rafinosa 25,62,66 .…”
Section: Composiciónunclassified